the role of notch signaling pathway in the development of craniofacial structures - Carbonell-Medina, Belfran Alcides (Revista Facultad de Odontología Universidad de Antioquia, 2014)
The NOTCH signaling pathway is a cell-cell signaling mechanism evolutionarily conserved among species, which is essential for proper embryonic development as it participates in a variety of cellular processes such as proliferation, differentiation, apoptosis, epithelial- mesenchymal transformation, migration, angiogenesis, stem cell maintenance, and cell fate determination. Several genes of this pathway have been implicated in the development of craniofacial structures. 80% of Alagille syndrome patients have mutations in the gene that codes for receptor Jagged1 (Jag1), along with midface hypoplasia and sporadic craniosynostosis. Mice with gene Jagged2 (Jag2) homozygous mutations present cleft palate as a result of ectopic fusions between the tongue and palatal processes. Similarly, mutations induced in the Hes1 gene produce developmental defects in craniofacial structures resulting from cranial neural crest cells (CrnNC), including cleft palate, frontal bone agenesis, cranial base malformation, and reduced size of upper and lower maxilla. Recent studies have shown alterations during tooth morphogenesis in Jagged2-/- mutant mice, accompanied by defects in ameloblasts cytodifferentiation and poor enamel matrix deposition. These studies show that NOTCH signaling pathway is involved in the development of a variety of craniofacial structures such as palate, teeth, maxillaries, and skull. The purpose of this article is to review the different functions of NOTCH signaling during the development of these craniofacial structures and the alterations resulting from mutations in some NOTCH signaling genes such as Jagged2, Jagged1, Hes1, Notch1, and Notch2.